BOOST YOUR PASSIVE INCOME BY BECOMING STOCKPRENEURIN CAPITAL MARKET - Setiyadi, Teguh; Rahmaniah, Fairdauzi Aulia (Universitas Pandanaran, 2023)
The desire to increase passive income as an alternative to obtain returns inaddition to the main income from active income, also considering the increasingnumber of trading platforms on various social media, encourages us as students of theManagement Study Program, Pandanaran University, Semarang, who have indeedbeeninvolved in the world of passive income for some time to hold a national seminar oncapital markets in more depth for other students who are included in the millennial generation to better understand the world of capital markets and understand howtomake safe passive income investments, especially stock investments by minimizingthelevel of risk that will be faced when investing and making choices to determine asafetrading platform according to the conditions of the investor. There needs to be an introduction to the capital market as early as possible forthe millennial generation, or the general public. In this introduction, students of theManagement Study Program at Pandanaran University in collaboration with IDXhelda national seminar entitled